Characterization of the biochemical composition and antioxidant activity of Spinacia oleracea L. and Spinacia turkestanica Iljin.: a comparative study - D. V. Sokolova; A. E. Solovieva (Овощи России, 2023)
Spinach is an economically important vegetable crop widely cultivated and consumed worldwide. This early ripening leafy vegetable is rich in bioactive components, fiber, micro and macro elements, vitamins, and has high antioxidant activity. Results of numerous studies on the effects of spinach on human health confirm its beneficial effect. The species S. oleracea L. is cultivated commercially. The ancestor of cultivated spinach is S. turkestanica Iljin, which has a breeding potential for different economically valuable traits. Its biochemical composition has been studied extremely little. The present article offers a comparative evaluation of the biochemical profile and antioxidant activity of cultivated and wild spinach species. The material for the study was a representative sample of 48 collection accessions of spinach from the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR). The accessions were grown in 2019 and 2020 in the open ground of the Pushkin and Pavlovsk Laboratories of VIR. The antioxidant activity was studied spectrophotometrically by the DPPH assay of free radical scavenging at a wavelength of 515 nm. A significant similarity of the two species in most biochemical parameters was revealed, which confirms their phylogenetic relationship. Significant differences were found in the content of phenolic elements, which determine the elevated values of antioxidant and antiradical activity of S. turkestanica. The article presents correlation matrices of species biochemical composition, describes general trends, negative relationships and conjugated factors. The identified promising accessions of both cultivated and wild spinach are recommended for breeding for increased content of phenolic compounds, ascorbic acid and antioxidant activity. The result of the study helps to reveal the potential of the crop as a valuable source of bioactive components and high antioxidant activity.